Very low birth weight infants in a Portuguese Neonatal Intensive Care Unit: a comparative study with the Vermont Oxford Network - Ana R. Fernandes; Paulo Soares; Gorett Silva; Filipa Flor-; Maria Beatriz Guedes; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2022)
Introduction: It is our goal to analyze the neonatal data from a Level III Unit and compare them with the overall data from the Vermont Oxford Network (VON).  Methods: It is an observational, retrospective study that included very low birth weight infants (VLBWI) born in this hospital or admitted in the first 24 hours of life between 2000 and 2013. Two periods, 2000-2006 and 2007-2013, were studied. Descriptive data and Chi-Square test were performed, and a value of p < 0.05 was considered statistically significant.  Results: A total of 607 VLBWI were studied, 51.1% male, mean weight 1,120 g and gestational age 29.3 weeks. Non-invasive ventilation in the Neonatal Intensive Care Unit (NICU) of Centro Hospitalar Universitário de São João (CHUSJ) was 63.5% in the 2000-2006 period and 70.2% in the 2007-2013 period, but still less than in the VON. Late-onset sepsis was 18.4% and 9.9% in the first and the second period, respectively, and 7.7% and 4.9% in the VON. Regarding mortality, it was higher in both periods in our NICU with respect to the VON, with a difference of 46.0% and 58.7% in the first and the second period, respectively.  Discussion: There were improvements regarding the use of mechanical ventilation and the incidence of late-onset sepsis. Both decreased between the two periods but were still having higher levels than those of the VON. Regarding morbidity and mortality, the difference may be explained by the fact that our NICU is Level III and a reference center for metabolic, oncological, cardiac and surgical pathologies.  Conclusion: It is very important for a NICU to know the characteristics of its population to assess the quality of healthcare and compare its results with other NICUs. VON allows us to identify the more and less positive aspects in order to improve the latter ones, and to promote better practices of healthcare.